Glycolipids from seaweeds and their potential biotechnological applications - Plouguerné, Erwan; da Gama, Bernardo A. P.; Pereira, Renato C.; Barreto-Bergter, Eliana (Frontiers in Cellular and Infection Microbiology, 2014)
Marine macroalgae, or seaweeds, are a formidable source of natural compounds with diverse biological activities. In the last five decades it has been estimated that more than 3,000 natural compounds were discovered from these organisms. The great majority of the published works have focused on terpenoids. In comparison, glycolipids are a neglected class of macroalgal secondary metabolites therefore remaining as a largely unknown reservoir of molecular diversity. Nevertheless, the interest regarding these compounds has been growing fast in the last decades as activities of ecological or pharmaceutical interest have been highlighted. This paper will review recent work regarding isolation and structural characterization of glycolipids from seaweeds and their prospective biological activities.